1992
DOI: 10.1038/ki.1992.27
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thromboxane synthase inhibition with CGS 13080 in human cyclosporine nephrotoxicity

Abstract: Cyclosporine is a potent immunosuppressive agent, however, its use is limited by nephrotoxicity. Increased production of the potent vasoconstrictor thromboxane A2 contributes to cyclosporine nephrotoxicity in animal models, but the role of thromboxane in human cyclosporine nephrotoxicity has not been established. We therefore studied cyclosporine-treated renal allograft recipients who had evidence of toxicity manifested by decreased renal function. We measured GFR and PAH clearance (CPAH) before, during, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…A decrease in renal blood flow appears to be one of the mediators of the toxic effect of CsA on the kidney [9], The precise etiology is unknown, but proposed mechanisms in-elude alterations in renal sympathetic nervous activity [2], changes in intrinsic renal vascular reactivity [3,4], and al terations in renal production of prostaglandins, especially TXA2 [5], The endothelial cell injury has been also suspect ed to be especially mediated through the thrombotic microangiopathy that occurs following CsA treatment [10].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in renal blood flow appears to be one of the mediators of the toxic effect of CsA on the kidney [9], The precise etiology is unknown, but proposed mechanisms in-elude alterations in renal sympathetic nervous activity [2], changes in intrinsic renal vascular reactivity [3,4], and al terations in renal production of prostaglandins, especially TXA2 [5], The endothelial cell injury has been also suspect ed to be especially mediated through the thrombotic microangiopathy that occurs following CsA treatment [10].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TxA 2 and PGI 2 or PGE 2 may represent a labilizing/stabilizing pair of endogenous humoral substances [25]. It has been demonstrated that administration of PGE analogues prevented or attenuated various toxic events induced by CyA [26,27], similarly TxA 2 synthase inhibitors and TxA 2 receptor antagonists were also reported to be useful in attenuating various toxic effects of CyA [28][29][30]. However, to our knowledge, there is no literature about the role of PGs in the effect of CyA preparations on the gallbladder.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vivo studies have suggested that to target thromboxane receptor can attenuated renal injury in experimental model of lupus [35]. Also, to block thromboxane receptor and thromboxane synthesis through inhibiting thromboxane synthase can play protective roles in cyclosporine-induced nephrotoxicity in experimental model [36] and in patients with deteriorated renal allograft function [37]. Taken together, relatively high-dose of rebamipide might be translated in renal injury of which the pathogenesis of which is involved in enhanced thromboxane signal, while low-dose of rebamipide might work as anti-inflammatory and anti-oxidant drug in chronic inflammatory and degenerative diseases.…”
Section: δ1214mentioning
confidence: 99%